THE LASER POWER OF LOW IN DIABETIC ULCER (Fiep Bulletin - online, 2013)
Diabetic ulcers normally present high healing intricacy. With that in mind, this study is proposed in the hope to identify some benefits in treating the pathology using low-power 660nm laser. Considering that diabetes is a pathology that affects many people throughout their lives, specially the elderly, it is possible to identify more expressive benefits when treating vascular lesions using 660nm laser which could avoid stump amputation caused by ulcers. The objectives derived in understand theoretical concepts on the benefits of using 660nm low-power laser to treat diabetic elderly patients. The use of laser-therapy in stimulating intense luminous monochromatic diode light ray in inflammatory healing from maturity and demodulation to total wound cure can be an efficient alternative in a pathological treatment.
Keywords: Diabetic Ulcer Treatment Benefit Low; Power Laser